Investigación en enseñanza de la física experimental en el siglo XXI - Riveros, Héctor G. (Revista Mexicana de Física E, 2017)
The aims of physics education have evolved alongside the society in which we live, to be able to adapt to the rapid pace of change imposed by the application of scientific discoveries in the industry. We could define the quality of physics’ teaching as its ability to learn how to reason. This approach covers both teaching competency-based and is student-centered. Each topic should be an excuse to teach how deduce it or induce it. The teacher decides if he/she deduces it or induces it from a demonstration or from experimental data. Experiments allows us to appreciate the ability of reasoning of the students, since they need to combine all they know in conducting the experiment. To evaluate the learning of a topic, we need to write questions to test the required reasoning, that it is not easy. PISA succeeds for students 15 years old, the challenge is to do it with our students.